2011
DOI: 10.1038/msb.2011.7
|View full text |Cite
|
Sign up to set email alerts
|

RNAi screen of Salmonella invasion shows role of COPI in membrane targeting of cholesterol and Cdc42

Abstract: A genome wide RNAi screen identifies 72 host cell genes affecting S. Typhimurium entry, including actin regulators and COPI. This study implicates COPI-dependent cholesterol and sphingolipid localization as a common mechanism of infection by bacterial and viral pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
103
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(110 citation statements)
references
References 97 publications
(159 reference statements)
7
103
0
Order By: Relevance
“…Using flow cytometry and confocal microscopy, we showed that Salmonella targeted mitotic cells more efficiently than cells in other phases of their cell cycle ( (Misselwitz et al, 2011). This was true for the different wild-type strains (12023, SL1344 and LT2) and cell lines tested (supplementary material Fig.…”
Section: Salmonella Invades Mitotic Cells Preferentiallymentioning
confidence: 89%
“…Using flow cytometry and confocal microscopy, we showed that Salmonella targeted mitotic cells more efficiently than cells in other phases of their cell cycle ( (Misselwitz et al, 2011). This was true for the different wild-type strains (12023, SL1344 and LT2) and cell lines tested (supplementary material Fig.…”
Section: Salmonella Invades Mitotic Cells Preferentiallymentioning
confidence: 89%
“…For example, Shigella uses its IpaB effector protein to bind the host raft‐associated CD44 transmembrane receptor (Lafont et al , 2002); entry of Listeria monocytogenes into host cells requires the localization of the host receptors E‐cadherin and HGF‐R/Met in specific lipid domains (Seveau et al , 2004). In addition to receptors, plasma membrane composition itself, specifically cholesterol and sphingolipid membrane content, impacts the binding and internalization of various bacterial pathogens, including Shigella and Salmonella species (Garner et al , 2002; Lafont et al , 2002; Misselwitz et al , 2011a; Santos et al , 2013). …”
Section: Introductionmentioning
confidence: 99%
“…On average, B2,400 cells were analysed per well and replicate. A Caenorhabditis elegans miRNA (cel-miR-231) with no sequence homology to any known human miRNA was used as the negative control in all experiments; a short interfering RNA (siRNA) against ACTR3, a protein important for the entry of Salmonella into host cells 17 , was used as the positive control ( Supplementary Fig. 1d).…”
Section: Screening For Mirnas Controlling Salmonella Infectionmentioning
confidence: 99%
“…The use of RNA interference screenings has improved our knowledge of the interplay between bacteria and host cells, identifying novel cellular factors critical for infection [17][18][19] . Only recently this approach has been extended to miRNAs 20,21 , and is yet to be applied for the identification of miRNAs critical for infection by bacterial pathogens.…”
mentioning
confidence: 99%